Gravitational instability of mantle lithosphere and core complexes. Issue 3 (20th March 2015) - Molnar, Peter
Abstract For a wide range of viscosity structures, convergent and downward flow of the mantle lithosphere during the growth of gravitational instability induces not only thickening of overlying crust but also concurrent horizontal extension in the upper crust. Such extension, if it occurred in the Earth, would include normal faulting of the upper crust above a region of horizontal shortening in the lower crust and uppermost mantle. Convergent flow in the lower crust would also create shear stress on horizontal planes and localized upward flow of the lower crust. These features—extension of upper crust and exhumation of strained lower crust—characterize metamorphic core complexes exposed in regions of normal to thick continental crust. Thus, convergent flow and downwelling mantle lithosphere might contribute to the development of core complexes, at least in some settings. If horizontal shortening and crustal thickening at depth do occur simultaneously with normal faulting at the surface of the Earth today, evidence of this process does not seem obvious, but perhaps it has occurred concurrently with widespread regional crustal extension in places like the Basin and Range Province, Tibet, the Pamir, or the Aegean. If such mantle flow does participate in the development of core complexes, a weak lower crust might not be a prerequisite for their formation.